(untitled) (Global Journal of Human-Social Science, 2023)
Revisions and Alternatives What are the foundations for a renewed political thought is a recent book by the human rights activist physician and politician Moncef Marzouki The book was published in Arabic by Arab Centre for Research Policy Studies in Doha It consists of 312 pages starting with a preface by Faisal Al-Qasim a British-Syrian anchor of political and cultural programs based in Qatar followed by four chapters Evaluation Update Challenges and Resources The book s central question is To what extent can the citizens and the state s visions and attitudes rooted in these five major ideologies threaten the human project in the contemporary capitalist technological global village